Evaluation of Tire-Pavement Contact Stress Distribution of Pavement Response and Some Effects on the Flexible Pavements - Nega, A.; Nikraz, Hamid (AMER SOC CIVIL ENGINEERS, 2017)
© ASCE. Pavement distress mechanisms become more prevalent in recent years such as surface rutting and surface initiated wheel path cracking. The main objective of this study is to evaluate tire-pavement contact stress distribution of pavement response using finite element analysis. It also assesses some of the effects of tire related factors on tire contact pressures and its response on flexible pavement. Tire-pavement contact stress is simulated using 3-D finite element method in ABAQUS for five layers of flexible pavement at various loads. 40 kN wheel load to represent a set of dual tires were assumed to be uniformly distributed over the contact area between tire-pavement surface. Four different tire-inflation pressures (350, 490, 630, and 700 kPa) were used to investigate some of the effects of tire-pavement structure. The finite element (FE) model analyses were verified with experiment results. Results have shown that contact stresses vary significantly for the different types of tire-pavement contact that were investigated. The tire's finite element was validated using measured contact area and deflection.